2023
DOI: 10.1371/journal.pone.0293031
|View full text |Cite
|
Sign up to set email alerts
|

CONcreTEXT norms: Concreteness ratings for Italian and English words in context

Maria Montefinese,
Lorenzo Gregori,
Andrea Amelio Ravelli
et al.

Abstract: Concreteness is a fundamental dimension of word semantic representation that has attracted more and more interest to become one of the most studied variables in the psycholinguistic and cognitive neuroscience literature in the last decade. Concreteness effects have been found at both the brain and the behavioral levels, but they may vary depending on the constraints of the context and task demands. In this study, we collected concreteness norms for English and Italian words presented in different context sente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…This intriguing finding may signify heightened demands on working memory, as the parietal P3 is widely recognized as a marker of working memory updating (Courchesne et al, 1975;Dien et al, 2004;Donchin, 1981;Friedman et al, 2001;Goldstein et al, 2002). The complexity inherent in more abstract concepts, with their multitude of meanings and variable concreteness degrees (Montefinese et al, 2023), imposes a substantial cognitive load. Selecting the correct meaning within memory and subsequently gauging the degree of concreteness becomes a more intricate task, demanding increased resources from working memory.…”
Section: Fine-grained Concreteness Effect In the P3-like Componentmentioning
confidence: 96%
“…This intriguing finding may signify heightened demands on working memory, as the parietal P3 is widely recognized as a marker of working memory updating (Courchesne et al, 1975;Dien et al, 2004;Donchin, 1981;Friedman et al, 2001;Goldstein et al, 2002). The complexity inherent in more abstract concepts, with their multitude of meanings and variable concreteness degrees (Montefinese et al, 2023), imposes a substantial cognitive load. Selecting the correct meaning within memory and subsequently gauging the degree of concreteness becomes a more intricate task, demanding increased resources from working memory.…”
Section: Fine-grained Concreteness Effect In the P3-like Componentmentioning
confidence: 96%
“…In fact, "side" has a medium concreteness score with a fairly high standard deviation, suggesting that judgments about the two senses of "side" are conflated in the final concreteness score. Recent studies have started to release datasets of concreteness ratings collected on words shown in context (Montefinese et al, 2023), tackling the different senses outlined above. However, there are other contextual factors that impact the perceived concreteness of a concept, including the actions that are performed with it: is the concreteness of "apple" the same, when we read "I imagined an apple" and "I bit an apple"?…”
Section: Dissent #3 For Concrete/concreteness (Bolognesi)mentioning
confidence: 99%